Analisis SWOT Sebagai Strategi Meningkatkan Daya Saing Pada Lim’s Cafe and Resto Tebing Tinggi - Sri Winda Hardiyanti Damanik; Novia Endiyani; Rakhmawati Purba (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
In determining the marketing strategy of a business requires the right tools/methods, one of which is using a SWOT analysis. SWOT analysis is an analysis of four elements consisting of strengths, weaknesses from the internal environment, opportunities and threats from the external environment. This study aims to determine the SWOT analysis strategy in increasing competitiveness at Lim's Cafe and Resto Tebing Tinggi. This type of research is descriptive qualitative with data obtained from both field data and literature processed through three stages, namely exposure of data based on the systematics that have been described (display), selecting and sorting data relevant to the discussion (reduction) and drawing conclusions (conclusion). ). The method used is Triangulation, namely Triangulation of Sources, Techniques and Theory. The results of the study, the internal factors of Lim's Cafe and Resto Tebing Tinggi have a value of 3.35 indicating the company's strategy in utilizing strengths and minimizing weaknesses is above average and internal conditions at this company tend to be strong and external factors of Lim's Cafe and Resto Tebing Tinggi have the value of 2.60 indicates the company's strategy in taking advantage of external opportunities and avoiding threats that will affect the company is above average and external conditions in this company tend to be strong. From the results of the comparison of the internal and external sectors, the company's ability to compete is in an aggressive growth strategy position, which is to make optimal use of the strengths and opportunities it has.